Innovation Adoption, Implementation and the Impact on Public Sector Performance: An Analysis Using SEM Modeling for Ethiopia - Solomon, Bereket (African Journal of Leadership and Development, 2021)
Innovation in the public sector has become mandatory in the current globalized economy and turbulent environment. Using the cross-section sample of 743 employees and management officials of public sector organizations at the Federal and Addis Ababa City Administration in Ethiopia, the study explores the level of innovativeness and the barriers as well as driving factors of innovation. A mixed methods research design has been employed with an emphasis on quantitative data using a structural equation model (SEM). The findings reveal that there is evidence of the adoption and implementation of innovation practices in the civil service sectors of Ethiopia. The results confirm that innovation significantly and positively affected organizational performance. Government expectation, customer demand, and globalization are the major driving forces of innovation in the civil service sector. Lack of incentives and protection along with inappropriate organizational culture and structure are the major barriers to innovation in the public sector. The policy implication is that the government should design innovation policy and strategy and the civil service organizations should create appropriate organizational culture and structure to nurture faster innovation.